Peran Hukum Organisasi Internasional Melalui Perserikatan Bangsa-Bangsa untuk Mengatasi Kejahatan Perang dalam Konflik Bersenjata antara Israel dan Palestina di Jalur Gaza - Dewa Made Yuda Dwi Artana; I Putu Dwika Ariestu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In international relations, it is very necessary to pay attention to what a country can and cannot do when interacting with other countries as a form of respect for sovereignty and international norms. Relations between countries in international life also include the involvement of international organizations that have an important role in maintaining global stability. In accordance with the goal of international organizations to resolve conflicts between countries, one of the conflicts that must be of concern to the world is armed conflict. One of the wars that is still in the spotlight to this day is the war between Israel and Palestine in the Gaza Strip. The research method used in this article is a normative legal research method with a literature approach and a case approach, namely related to war crimes in the Israeli-Palestinian conflict in the Gaza Strip. The United Nations as part of an international organization within the framework of the Law of the International Organization has made various efforts to maintain peace in Palestine. However, because this war is one of the most complicated, protracted, and fraught with international political importance, its resolution still faces various obstacles that make it difficult to end the conflict to this day.